GTP-binding protein Di-RAS3 diminishes the migration and invasion of non-small cell lung cancer by inhibiting the RAS/extracellular-regulated kinase pathway. Issue 3 (1st March 2022) - Kuang, Peng; Xie, An; Deng, Jianxiong; Tang, Jiaming; Wang, Peijun; Yu, Feng
ABSTRACT: The GTP-binding protein Di-Ras3 (DIRAS3) has been established as a maternally imprinted tumor suppressor gene. Growing evidence has correlated the DIRAS3 gene with tumor progression, but its role in non-small cell lung cancer (NSCLC) is rarely reported. Accordingly, the current study sought to evaluate the role and mechanism of DIRAS3 in NSCLC cell progression. First, we uncovered that DIRAS3 was poorly expressed in NSCLC tissues and cells. Subsequently, we examined the effect of DIRAS3 over-expression or knockdown in different lung cancer cells on their malignant phenotypes, with the help of transwell cell migration and invasion assays, and Western blot analyses. It was found that the over-expression of DIRAS3 inhibited the migration and invasion of A549 cells or H520 cells, whereas knockdown of DIRAS3 led to opposing trends. In addition, over-expression of DIRAS3 attenuated the tumor growth and reduced the number of lung tumor nodules. Mechanistically, DIRAS3 may inhibit the migration and invasion of NSCLC cells by inhibiting the RAS/extracellular-regulated kinase (ERK) signaling pathway. Collectively, our findings indicate that DIRAS3 could serve as a potential therapeutic target biomarker for NSCLC. Graphical abstract: uf0001